КЛИНИКО-ЛАБОРАТОРНЫЕ ОСОБЕННОСТИ МУЛЬТИСИСТЕМНОГО ВОСПАЛИТЕЛЬНОГО СИНДРОМА У ДЕТЕЙ - Рагимова, Наиля Джалил; Мирсалаева, Лейла Шамсаддин; Ашрафова, Кенуль Назим; Насирова, Севиндж Рамиз (FORCIPE, 2022)